Cold range edges of marine fishes track climate change better than warm edges. (12th March 2020) - Fredston‐Hermann, Alexa; Selden, Rebecca; Pinsky, Malin; Gaines, Steven D.; Halpern, Benjamin S.
Abstract: Species around the world are shifting their ranges in response to climate change. To make robust predictions about climate‐related colonizations and extinctions, it is vital to understand the dynamics of range edges. This study is among the first to examine annual dynamics of cold and warm range edges, as most global change studies average observational data over space or over time. We analyzed annual range edge dynamics of marine fishes—both at the individual species level and pooled into cold‐ and warm‐edge assemblages—in a multi‐decade time‐series of trawl surveys conducted on the Northeast US Shelf during a period of rapid warming. We tested whether cold edges show stronger evidence of climate tracking than warm edges (due to non‐climate processes or time lags at the warm edge; the biogeography hypothesis or extinction debt hypothesis ), or whether they tracked temperature change equally (due to the influence of habitat suitability; the ecophysiology hypothesis ). In addition to exploring correlations with regional temperature change, we calculated species‐ and assemblage‐specific sea bottom and sea surface temperature isotherms and used them to predict range edge position. Cold edges shifted further and tracked sea surface and bottom temperature isotherms to a greater degree than warm edges. Mixed‐effects models revealed that for a one‐degree latitude shift in isotherm position, cold edges shifted 0.47 degrees of latitude, and warm edges shifted only 0.28 degrees. Our results suggest that cold range edges are tracking climate change better than warm range edges, invalidating the ecophysiology hypothesis. We also found that even among highly mobile marine ectotherms in a global warming hotspot, few species are fully keeping pace with climate. Abstract : We analyzed annual range edge dynamics of marine fishes using 50 years of trawl surveys from the Northeast US Shelf during a period of rapid warming. We tested whether cold edges show stronger evidence of climate tracking than warm edges (due to non‐temperature processes or time lags at the warm edge), or whether they tracked temperature equally (due to the influence of habitat suitability). Cold edges shifted further and tracked temperature to a greater degree than warm edges. We also found that even among mobile marine ectotherms in a global warming hotspot, few species are fully keeping pace with climate.